2021
DOI: 10.1590/1807-1929/agriambi.v25n3p156-162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beneficial microorganisms on upland rice performance

Abstract: Inoculating plants with a mix of beneficial microorganisms can significantly improve plant growth and contribute to sustainable agriculture. However, it is unclear if mixed inoculations of microorganisms provide better results than inoculations of a single beneficial microorganism. Thus, the objective of this study was to evaluate the effects of beneficial microorganisms on the performance of upland rice in a greenhouse experiment using a completely randomized design with three repetitions and 26 treatments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…J. Fernandes et al (2021b) also recorded a higher total biomass for upland rice co-inoculated with Ab-V5 + BRM 63573. Similarly, Braga et al (2018) showed that soybean inoculation with Bacillus subtilis increased shoot and root dry biomasses.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…J. Fernandes et al (2021b) also recorded a higher total biomass for upland rice co-inoculated with Ab-V5 + BRM 63573. Similarly, Braga et al (2018) showed that soybean inoculation with Bacillus subtilis increased shoot and root dry biomasses.…”
Section: Resultsmentioning
confidence: 90%
“…They can provide greater root diameter of seedlings (J. P. T. Fernandes et al, 2021a) and higher biomass production (J. Fernandes et al, 2021b) in upland rice plants, compared to the control treatment (without rhizobacteria). Other studies have also shown that more than one multifunctional rhizobacterium can be inoculated into plants using a technique called co-inoculation (M. A.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show the beneficial effects of multifunctional microorganisms in increasing shoot dry biomass and productivity of soybean (SILVA et al, 2020b;CHAGAS JUNIOR et al, 2022) and common bean (Phaseoulus vulgaris) (REZENDE et al, 2021a); growth promotion of rice (Oryza sativa L.) (FERNANDES et al, 2021;PARRALES et al, 2022) and accumulation of N in maize plants (Zea mays) (MORENO et al, 2021). In addition, the use of different beneficial microorganisms at the same time, defined as coinoculation or consortium of microorganisms, has been gaining market share, since it adds different mechanisms of action, producing potential synergistic effects, compared to the use of isolated microorganisms (FLAUZINO et al, 2018).…”
Section: Introductionmentioning
confidence: 99%